Decreased Langerhans Cell Responses to IL-36γ: Altered Innate Immunity in Patients with Recurrent Respiratory Papillomatosis - DeVoti, James (ScholarOne, 2014)
Recurrent respiratory papillomatosis (RRP) is a rare, chronic disease caused by human papillomaviruses (HPVs) types 6 and 11 that is characterized by the polarization of adaptive immune responses that support persistent HPV infection. Respiratory papillomas express elevated mRNA levels of IL-36γ, a proinflammatory cytokine in comparison to autologous clinically normal laryngeal tissues; however there is no evidence of inflammation in these lesions. Consistent with this, respiratory papillomas do not contain T(H)1-like CD4(+) T-cells or cytotoxic CD8(+) T-cells, but instead contain a predominance of T(H)2-like and T regulatory cells (Tregs). In addition, papillomas also are infiltrated with immature Langerhans cells (iLCs). In this study, we show that papilloma cells express IL-36γ protein, and that human keratinocytes transduced with HPV11 have reduced IL-36γ secretion. We now provide the first evidence that peripheral blood-derived iLCs respond to IL-36γ by expressing inflammatory cytokines and chemokines. When stimulated with IL-36γ, iLCs from patients with RRP had lower expression levels of the T(H)2-like chemokine CCL-20 as compared with controls. Patients’ iLCs also had decreased steady state levels of CCL-1, which is a proinflammatory chemokine. Moreover, CCL-1 levels in iLCs inversely correlated with the severity of RRP. The combined decrease of T(H)1- and a T(H)2-like chemokines by iLCs from patients could have consequences in the priming of IFN-γ expression by CD8(+) T-cells. Taken together, our results suggest that, in RRP, there is a defect in the proinflammatory innate immune responses made by iLCs in response to IL-36γ. The consequence of this defect may lead to persistent HPV infection by failing to support an effective HPV-specific, T(H)1-like and/or T(c)1-like adaptive response, thus resulting in the predominant T(H)2-like and/or Treg micromilieu present in papillomas.